Joe Biden's policies on abortion and immigration: the challenges of a Catholic president - Formicola, Jo Renée (Lexington Books, 2024)
Cover -- Contents -- Introduction -- From Roe to Dobbs -- From Dobbs Forward -- Catholics, Biden, and Immigration -- Pyrrhic Victories -- Leading and Governing -- Epilogue -- Bibliography -- Index -- About the Author.